The Development of Khanom-Pum with Sangyod Rice Replacement - Chumkaew, Krittin; Phuenjcome, Orawan; Punfujinda, Chaiyasit (Journal of Food Health and Bioenvironmental Science, 2019)
The objectives of this research were to develop a basic recipe of Khanom-Pum and investigate the proper amount of Sangyod rice suitable for cooking Khanom-Pum. In addition, physical quality, chemical analysis and customers’ acceptance of the Khanom-Pum were studied. The results indicated that the proper basic recipe consisted of rice flour, liquid Palmyra palm sugar, and water with the following proportion 24%, 40% and 36%, respectively. The best recipe of Khanom-Pum was 50% replacement with Sangyod rice. Hardness and lightness value (L*, a*, b*) decreaed with increasing the levels of Sangyod rice. The chemical analysis of the Khanom-Pum was 50% covered moisture, protein, fat, fibers, ash and carbohydrates in the following percentage of 1.47, 48.03, 0.12, 1.34, 0.76 and 48.28, respectively and vitamin B1 was 1.06 mg per 100 g. The Khanom-Pum with 50% Sangyod rice flour had more fibers and vitamin B1 than in the basic recipe. In terms of customer acceptance, there were 100 respondents. The results revealed the level of overall satisfaction was at the high level. Regarding future purchase, 94% would buy the product if the product was available in the market. Approximately 75% reasoned that the Khanom-Pum was healthy and 80% accepted the product at the highest level.